2023
DOI: 10.1192/j.eurpsy.2023.2416
|View full text |Cite
|
Sign up to set email alerts
|

Effects of strict COVID-19 lockdown on patients with obsessive-compulsive disorder compared to a clinical and a nonclinical sample

Abstract: Background Symptoms of obsessive-compulsive disorder (OCD) have been reported to increase during the COVID-19 lockdowns because of the hygiene requirements related to the pandemic. Patients with adjustment disorder (AD) may, in turn, represent a vulnerable population for identifiable stressors. In this study, we aimed at assessing potential symptoms changes in OCD patients during the lockdown in comparison with AD patients as well as versus healthy controls (HC). Methods During the COVID-related lockdown, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…Although these findings are consistent with the findings of some studies [ 50 ], most previous studies have reported that psychiatric patients, especially those with SPDs, experienced more anxiety than the general population [ 31 33 ]. One explanation is that pre-existing symptoms exacerbated their anxiety in the face of the pandemic [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Although these findings are consistent with the findings of some studies [ 50 ], most previous studies have reported that psychiatric patients, especially those with SPDs, experienced more anxiety than the general population [ 31 33 ]. One explanation is that pre-existing symptoms exacerbated their anxiety in the face of the pandemic [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Stressful factors such as fear of death, fear of losing loved ones, loss of social connection, and loss of employment may even cause severe psychological problems in formerly healthy people [ 52 ]. Some studies reported that healthy individuals had higher levels of anxiety and depression than individuals with SPDs during COVID-19 health crisis [ 51 ]. What further strengthens this interpretation is that participants without psychiatric disorders performed more safety behaviors in response to the pandemic than patients with OCD, or did not differ in this respect from patients with SSD, BD, and MDD.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations